The effects of hypoxia-inducible factor (HIF)-1α protein on bone regeneration during distraction osteogenesis: an animal study. Issue 2 (February 2016) - Jiang, X.; Zhang, Y.; Fan, X.; Deng, X.; Zhu, Y.; Li, F.
Abstract: The aim of this study was to observe the effect of hypoxia-inducible factor (HIF)-1α on bone regeneration during distraction osteogenesis (DO). Fifty-one New Zealand white rabbits underwent mandibular lengthening with a distraction rate of 2 mm/day, and were divided randomly into three groups (17 in each). Group C rabbits received 20 μg rHIF-1α, group B received 10 μg rHIF-1α, and group A received 100 μl saline injection in the distraction gap every day for 10 days. Radionuclide bone imaging (RBI), computed tomography, dual energy X-ray absorptiometry, radiography, histology, and three-point bend testing were performed. RBI showed that the uptake ratio in group B (1.41 ± 0.25, P  = 0.013) and group C (1.64 ± 0.37, P  < 0.001) was higher than that in group A (1.01 ± 0.26). The bone mineralization density and bone mineralization content in group C were highest among the three groups. Radiology and histology findings indicated more callus regeneration in groups C and B. Mechanical testing demonstrated that the ultimate force in group C (289.71 ± 43.31 N, n  = 6) was 1.49-fold ( P  < 0.001) that of group A and 1.20-fold ( P  = 0.012) that of group B. HIF-1α may represent a new agent to promote DO by accelerating osteogenesis and mineralization.